2019
DOI: 10.1111/apa.15015
|View full text |Cite
|
Sign up to set email alerts
|

Different thickening complexes with pectin in infant anti‐regurgitation formula

Abstract: Aim To summarise the results from four clinical trials assessing the efficacy and safety of a thickening complex in the management of regurgitation in infants. Methods Infants (n = 392) younger than 5 months presenting with at least five regurgitations per day were recruited in four open‐label, interventional, single‐group, multi‐centric clinical trials sharing an identical design. The efficacy of four different formulae thickened with different thickening complexes of pectin, starch and locust bean gum, was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Thickened formulas have high viscosity, which prevents the refluxate from reaching the upper part of the gastrointestinal tract, effectively reducing regurgitation. 82 Commonly used thickening agents include cereal starch, carob/locust bean gum and soybean polysaccharides. There is no evidence that one thickening agent is superior to others.…”
Section: Composition Of Human Milk and Different Infant Formulasmentioning
confidence: 99%
“…Thickened formulas have high viscosity, which prevents the refluxate from reaching the upper part of the gastrointestinal tract, effectively reducing regurgitation. 82 Commonly used thickening agents include cereal starch, carob/locust bean gum and soybean polysaccharides. There is no evidence that one thickening agent is superior to others.…”
Section: Composition Of Human Milk and Different Infant Formulasmentioning
confidence: 99%
“…This is a commonly used thickening or stabilization agent in the food industry [18][19][20][21]. It is believed that the soluble fibers of apples and citrus that are commonly made into jams, preserves, and dietary supplements can improve the digestive associated health and minimize some gastrointestinal and metabolic disorders [18,[22][23][24]. Additionally, pectin is a pharmaceutic ingredient to produce gel or gel capsules due to its minimal toxicity and low cost [20,25].…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy Pectin is a carbohydrate that just as LBG is not sensitive to digestion. Pectin is also fermented by the intestinal microbiota [2]. It has stabilizing, gelling, and thickening properties and is often used in food [2].…”
Section: Pectinmentioning
confidence: 99%
“…Pectin is also fermented by the intestinal microbiota [2]. It has stabilizing, gelling, and thickening properties and is often used in food [2]. In the past, multiple trials have shown a significant (P < 0.001) decrease of regurgitation episodes in infants fed a formula thickened with pectin [17][18][19][20].…”
Section: Pectinmentioning
confidence: 99%
See 1 more Smart Citation